A scoping review of substance use brief interventions in Africa. - Florence Jaguga; Sarah Kanana Kiburi; Eunice Temet; Matthew C Aalsma; Mary A Ott; Rachel W Maina; Juddy Wachira; Cyprian Mostert; Gilliane Kosgei; Angeline Tenge; Lukoye Atwoli (PLOS Global Public Health)
Background The burden of substance use in Africa is substantial. Brief interventions (BIs) are a recommended public health strategy for the prevention and early intervention for substance use problems. The objective of this scoping review was to map the literature on substance use BIs in Africa, identify gaps, and provide directions for future research. Methods The scoping review was guided by the Arksey O'Malley Framework and the PRISMA-Scoping review (PRISMA-ScR) guidelines. A search of five bibliographic databases (PubMed, PsychINFO, Web of Science, Cumulative Index of Nursing and Allied Professionals (CINAHL) and Cochrane Library) was conducted from inception until 1st November 2023. BIs were defined as those targeting substance use and delivered over 1-4 sessions, or interventions delivered over more than four sessions if the authors referred to them as 'brief'. Results of the review have been summarized descriptively and organized by three broad outcomes: BI effect and feasibility; feasibility and effectiveness of training providers to deliver BIs; Other outcomes i.e. cost-effectiveness, BI adaptation and development, and knowledge attitude and practice of BIs by providers. Results Of the 80 studies that were eligible for inclusion, 68 investigated the effect and feasibility of BIs, six studies investigated the feasibility and effectiveness of training providers to deliver BIs, and six explored other outcomes. Most of the available studies had been conducted in Eastern and Southern Africa. BIs were largely based on motivational interviewing and psychoeducational principles. Overall, the BIs were reported as feasible to implement from the perspective of policy makers, providers, and the intervention recipients. Findings on the effect of BIs on substance use were mixed. Key evidence gaps emerged. There was paucity of BI research focusing on substances other than alcohol, and there was limited literature on feasibility and efficacy of BIs among youth and adolescents. Conclusion The results of this scoping review provide important directions for future substance use BI research in Africa.